Terapia com Levamisole em crianças e adolescentes com Síndrome Nefrótica Córtico dependentes ou recidivantes frequentes: experiência de um centro de referência em Minas Gerais - Mariana Marta de Oliveira Antunes (2021)
Introduction: Corticosteroid-sparing therapy is the best strategy to reduce long-term steroid exposure in patients with nephrotic syndrome, and levamisole has been shown to be a low-cost, easily accessible, steroid-sparing agent with a low rate of adverse events. Objectives: To synthesize the literature evidence on steroid-sparing strategies in pediatric patients with nephrotic syndrome. To evaluate the response to the use of levamisole in pediatric patients with cortico-resistant nephrotic syndrome or frequent relapses. Methods: An integrative review of the evidence available in the literature regarding the use of steroid-sparing agents in pediatric patients with frequent relapsing or steroid-dependent cortico-sensitive nephrotic syndrome. Data collection of patients using levamisole to assess the response to medication. Results: There is no reference corticosteroid-sparing medication in the pediatric population. When necessary, steroid-sparing therapy should be individualized and shared with family members. Corticosteroid use remains the initial treatment of choice. Of the 30 patients selected for the study, 86.7% had no adverse effects with the use of levamisole. The most used corticosteroid sparing agent before the use of levamisole was cyclophosphamide (26.7%). Renal biopsy was performed in 30% of patients and the most common finding was focal segmental glomerulus sclerosis (FSGS), followed by minimal change disease. Over the course of the one-year evaluation, there was no worsening of any RBC index (P > 0.05) including neutrophils. Conclusions: In our study, levamisole showed efficiency in reducing the number of relapses in the first year of use, in addition to maintaining stability of renal function, with a low rate of adverse events.